(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article investigates corporate culture as a factor which form a facilitate reliable performance in relatively unstable environments. The study reviews the concept and approaches to the corporate culture. The research followed by methods, such as comparative analysis, synthesis, scientific abstraction. Practical implications. The study finds that an effective culture must be aligned with moral and psychological qualities of the employer and employee of the company. Research implications. The study shows that the corporate culture influence the performance of the organization and productivity of its employees. Further studies should examine the possible relationships between corporate culture and the strategy of the company among Ukrainian companies.